Epidemiological and clinical trends of sexually transmitted infections. Literature review - T.M. Tutchenko; O.A. Burka; I.F. Boyarchuk; A.V. Trampolska; V.V. Iavniuk; L.S. Ostroukh (Publishing House TRILIST, 2021)
This article presents modern data on epidemiological trends, pathogenesis, and mechanisms of persistence and acquisition of antibiotic resistance of the most common sexually transmitted infections (STIs): chlamydial infection, gonorrhea, trichomoniasis. Data on the frequency of chlamydial infection, gonorrhea, trichomoniasis detection in the DILA medical laboratory in the period from 2018-2020 are also presented. Analysis of epidemiological and microbiological studies indicates a significant increase in the STIs incidence in countries with high economic development and the need for constant revision of diagnostic and treatment approaches, based on new data on the pathogens physiology, mechanisms and levels of antibiotic resistance, possibilities of laboratory diagnostics. Analysis of the DILA data on the chlamydial infection, gonorrhea, trichomoniasis detection is coinciding with the world trends in the increase of their prevalence. At the same time, the analysis of the DILA data demonstrated an interesting clinical phenomenon as a presence of 2 STIs peaks in women: the first at 21-25 years and the second at 51-55 years old. Clinical manifestations of STIs are increasingly losing their typical features today. This indicates the need for a laboratory search for all common STIs in the region. Knowledge of the etiological factor of the inflammatory process allows choosing the correct antibiotic therapy and preventing the further development of antibiotic resistance. This article presents data on the various methods of STIs laboratory tests. Regular visits of women for cervical cancer screening are a good opportunity to screen for STIs. The ability to detect STIs in biomaterial in liquid cytology makes this option more accessible. Thus, since vaccines against common bacterial and protozoa STIs pathogens have not yet been developed, the promotion of hygiene of sexual behavior and timely detection of infected persons during examination or screening with subsequent etiopathogenetic treatment are the basis of the STIs control systems and their consequences prevention.